TRANSFORMASI KEHIDUPAN JEMAAT BERDASARKAN ROMA 12 2 DALAM KAJIAN TEOLOGI DAN SOSIOLOGI KRISTEN - Rahelia Tirani Banten; Harun Artha Christovany; Riandi; Andre Yusuf Biu; Miktam Pasorong (ADISAM PUBLISHER, 2026)
This study aims to analyze the transformation of the congregation's life based on Romans 12:2 from the perspectives of Christian theology and sociology. It employs a qualitative method using a literature review approach, examining the Bible, theological texts, works on Christian sociology, and relevant scholarly articles. The findings indicate that Romans 12:2 affirms transformation as a continuous process of renewing the mind through the work of the Holy Spirit, resulting in changes in character, mindset, and behavior that align with God's will. From a Christian theological perspective, transformation is understood as part of the sanctification process that makes believers increasingly Christ-like. Meanwhile, from the perspective of Christian sociology, transformation is reflected in the formation of community identity, the strengthening of social relationships, and the congregation's active involvement in embodying the values ​​of the Kingdom of God within society. The study also demonstrates that Romans 12:2 holds significant relevance in addressing contemporary challenges such as globalization, the rise of digital technology, individualism, and moral crises. Therefore, the church needs to develop discipleship and character-building programs centered on the Word of God, enabling the congregation to become agents of transformation who make a positive impact on both the church and society.